EKONOMSKA VREDNOST LIČNIH PODATAKA U DIGITALNOJ EKONOMIJI - Paskaleva, Mariya (International Journal of Economic Practice and Policy, 2025)
Personal data can be seen as an economic asset generated by the identity and behavior of individuals who are traded in exchange for higher-quality services and products. The volume of stored personal data is increasing rapidly. In the two-sided market mechanism, online platforms act as intermediaries that collect consumer data and sell advertising slots to companies. Using personal data removes information asymmetries and contributes to the efficiency of online transactions. Consumers' lack of self-determination of personal data can lead to the uneven exchange of economic value. Unless appropriate measures are taken, such concerns about how data is used threaten to reduce individuals' willingness to share their personal information. Personal data can help businesses perform 'churn detection', identifying customers more likely to leave a retailer. Using such techniques, companies can implement marketing actions to increase customer loyalty. Detecting customer churn is important for businesses because the cost of retaining existing customers is usually lower than the cost of acquiring new customers. Targeted Internet advertising plays a useful informational role for users, as they can see adverts relevant to their potential unique interests. Voluntary data sharing by users is accompanied by explicit rewards and other promotional offers In the current study we explore the advertisements by the online platforms and their relation with personal data transfer. To explore the economic value of personal data, we apply a survey. Correlation analysis is applied.
Keywords: Digital economy; Risk management; Personal data